Diskresi Aparat Satuan Polisi Pamong Praja dalam Penyelenggaraan Ketertiban Umum dan Ketenteraman Masyarakat - Erwanda Pratama; Kms. Novyar Satriawan Fikri; Herdiansyah Herdiansyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The Civil Service Police Unit (Satpol PP) plays a strategic role in maintaining public order as a regional government apparatus, requiring discretionary authority when legal provisions do not fully regulate field situations. This study analyzes the legal framework, implementation, and accountability limits of Satpol PP’s discretion from the perspective of General Principles of Good Governance (AUPB). Using a normative legal method with statutory, conceptual, and case approaches, this research examines legal materials through qualitative and interpretative analysis. The findings show that Satpol PP’s discretionary authority has a sufficient constitutional and administrative basis but lacks clear operational standards. Its implementation still faces procedural weaknesses, limited documentation, and insufficient consideration of social justice values. The exercise of discretion is limited by legality, procedure, proportionality, and justice principles, with accountability mechanisms available through internal supervision, administrative review, the Ombudsman, and the State Administrative Court. Strengthening rights-based procedures aligned with AUPB is recommended to ensure lawful, accountable, and humane public order enforcement.